2022
DOI: 10.3390/separations9030058
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Aflatoxin M1 in Various Origins Greek Milk Samples Using Liquid Chromatography Tandem Mass Spectrometry

Abstract: Aflatoxin M1(AFM1), a major metabolite of Aflatoxin B1(AFB1), has been identified as a potential contaminant in dairy products. Because of its possible carcinogenicity, the legislation limits as set by Commission Regulation (EC) No. 1881/2006 are very strict, namely 0.050 μg kg−1 in milk and 0.025 μg kg−1 in infant formulas. To meet these requirements, a sensitive and accurate method was developed, employing liquid chromatography tandem mass spectrometry (UPLC-MS/MS). Ιmmunoaffinity columns (R-Biopharm) were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Other authors have identified the occurrence of AFM1 in bovine milk in countries such as Nigeria, United Arab Emirates, Mexico and in derived products in Greece, China and West Asian countries (Mukhtar et al, 2022;Mohamadin et al, 2022;Álvarez-Dí as, 2022;Panara et al, 2022;Xiong et al, 2022). However, the lack of investigations into the occurrence of AFM1 in bovine milk in northern Brazil makes it difficult to monitor contamination in the state of Amazonas, despite reports of the presence of the mycotoxin in other Brazilian regions.…”
Section: Afm1mentioning
confidence: 99%
“…Other authors have identified the occurrence of AFM1 in bovine milk in countries such as Nigeria, United Arab Emirates, Mexico and in derived products in Greece, China and West Asian countries (Mukhtar et al, 2022;Mohamadin et al, 2022;Álvarez-Dí as, 2022;Panara et al, 2022;Xiong et al, 2022). However, the lack of investigations into the occurrence of AFM1 in bovine milk in northern Brazil makes it difficult to monitor contamination in the state of Amazonas, despite reports of the presence of the mycotoxin in other Brazilian regions.…”
Section: Afm1mentioning
confidence: 99%
“…Given the potential harm of AFM 1 , Brazil has adopted regulatory limits for this mycotoxin, with maximum permissible limits (MPL) of 0.5 µg/L for fluid milk and 2.5 µg/kg for cheese [ 15 ]. The occurrence and levels of AFM 1 in milk products have been monitored [ 14 ] using several analytical methods, comprising the popular enzyme-linked immunosorbent assay (ELISA) [ 16 ], high-performance liquid chromatography (HPLC) alone [ 17 ], and HPLC combined with tandem mass spectrometry (MS/MS) [ 18 ]. In this context, monitoring AFM 1 concentrations in milk and its derived products is an essential aspect of food safety efforts, aimed at protecting consumers’ health protection [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reliable, accurate, and sufficiently sensitive methods are required to detect and quantify cyano-and myco-toxins. A wide range of extraction and analytical methods have been developed [19,[27][28][29][30][31]. The first part of the sample treatment is the extraction.…”
Section: Introductionmentioning
confidence: 99%